Repeatability and Reproducibility of in-vivo Brain Temperature Measurements - Sharma, Ayushe A.; Nenert, Rodolphe; Mueller, Christina; Maudsley, Andrew A.; Younger, Jarred W.; Szaflarski, Jerzy P. (Frontiers in Human Neuroscience, 2020)
Background. Magnetic resonance spectroscopic imaging (MRSI) is a neuroimaging technique that can be used to noninvasively map brain temperature (i.e., thermometry) over a large brain volume. To date, intra-subject reproducibility of MRSI-based brain temperature (MRSI-t) has not been investigated. The objective of this repeated measures MRSI-t study was to establish intra-subject reproducibility and repeatability of brain temperature, as well as typical brain temperature range. Methods. Healthy participants aged 23-46 years (N=18; 7 females) were scanned at two time points, ~12-weeks apart. Volumetric MRSI data were processed by reconstructing metabolite and water images using parametric spectral analysis. Brain temperature was derived using the frequency difference between water and creatine (TCRE) for 47 regions of interest (ROIs) delineated by the modified Automated Anatomical Labeling (AAL) atlas. Reproducibility was measured using the coefficient of variation for repeated measures (COVrep), and repeatability was determined using the standard error of measurement (SEM). For each region, the upper and lower bounds of Minimal Detectable Change (MDC) were established to characterize the typical range of TCRE values. Results. The mean global brain temperature over all subjects was 37.2°C, with spatial variations across ROIs. There was a significant main effect for time (F(1, 1591)=37.0, p < 0.0001) and for brain region (F(46, 1591)=2.66, p<0.0001). The time*brain region interaction was not significant (F(46, 1591)=0.80, p=0.83)). Participants’ TCRE was stable for each ROI across both time points, with ROIs’ COVrep ranging from 0.81 – 3.08% (mean COVrep = 1.92%); 30 ROIs had a COVrep < 2.0%. Conclusions. Brain temperature demonstrated subtle regional variations that were highly consistent between both time points, indicating high reproducibility and repeatability of MRSI-t. MRSI-t may be a promising diagnostic, prognostic, and therapeutic tool for non-invasively monitoring pathological brain temperature changes when other modalities are unrevealing. However, further studies of healthy participants with larger sample size(s) and numerous repeated acquisitions are imperative for establishing a reference range of typical brain TCRE, as well as the threshold above which TCRE is likely pathological.